Leprosy in Denmark 1980–2010: a review of 15 cases. (December 2016) - Aftab, Huma; Nielsen, Susanne; Bygbjerg, Ib
Abstract Background Leprosy, caused byMycobacterium leprae, is a chronic and progressive granulomatous disease affecting mainly the skin and the peripheral nervous system. If left unrecognized, the infection can lead to permanent nerve damage and disability. The clinical presentation depends on the immune response of the patient and can result in a wide spectrum of symptoms. Leprosy is a rare encounter in Scandinavia but remains endemic in some parts of the world, with some areas reporting an increasing incidence. We performed a retrospective record review of leprosy cases in Denmark from 1980 to 2010 with the purpose of presenting the most common geographical, demographic and clinical findings and to discuss the diagnostic and therapeutic challenges of patients with leprosy. Case presentation In total 15 cases were reviewed. The majority (87 %) of leprosy patients in Denmark were born in South- and Southeast Asia, and were presumed to have contracted the infection in their countries of origin. Patients were predominately young males (mean age: 28.6 years). Anaesthetic skin lesion with or without nerve enlargement were the most common clinical presentations (73 %). Immunological leprosy reactions were seen in 40 % of the cases. Diagnoses were based on clinical findings and skin biopsies. Treatment length varied but all patients received multidrug regimens. Conclusion Leprosy should be kept in mind when encountering patients with suspicious skin lesions originating from leprosy endemic areas or with history of travel or work in the tropics. Due to the long incubation period with symptoms presenting long after immigration or return, clinicians often do not have the diagnosis in mind. The wide spectrum of symptoms and immunological reactions further complicates the diagnostic process. Treatment of leprosy and the complicated immunological reactions, which frequently accompanies the infection, should be performed in collaboration with a specialist.